2021
DOI: 10.26417/262yzc26s
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Female Volleyball Players in VO2max

Abstract: Aims: In volleyball the main achievement is winning the match so the tools and methods used during the training sessions are very important to achieve this goal. Purpose of the study is the identification of volleyball players in the development performance of i VO2max. Method: Test Astrand was used to evaluate VO2max in 75 female volleyball players in the average age of 17.1 years of the Albanian championship in two different periods _Pre and _Post mini phase of their training in the respective teams. Anthrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
1
Order By: Relevance
“…Further, Shete et al [ 38 ] followed a group of female athletes and non-athletes aged between 17 and 22 years and reported mean differences of 16 mL/min/kg between groups, against 5.5 mL/min/kg measured in our study sample. Other authors [ 39 ] reported on female volleyball athletes who were aged 17.1 years old, with values between 41.09 and 42.56 mL/min/kg, going against our outcomes, which failed to exceed 37.5 and 43 mL/min/kg. However, most results will differ depending on sports practice, age, and gender.…”
Section: Discussioncontrasting
confidence: 80%
“…Further, Shete et al [ 38 ] followed a group of female athletes and non-athletes aged between 17 and 22 years and reported mean differences of 16 mL/min/kg between groups, against 5.5 mL/min/kg measured in our study sample. Other authors [ 39 ] reported on female volleyball athletes who were aged 17.1 years old, with values between 41.09 and 42.56 mL/min/kg, going against our outcomes, which failed to exceed 37.5 and 43 mL/min/kg. However, most results will differ depending on sports practice, age, and gender.…”
Section: Discussioncontrasting
confidence: 80%
“…While Endurance is the determinant of an athlete's performance because of the repetitive activity and pressure that occurs (Bridel & Denison, 2016). Vo2Max volleyball athletes are trained based on typical endurance according to the game (spiking, jumping, power hit, blocking setting), so that aerobic capacity can be optimal (Lleshi, 2021). Elements of biomotor complexity and variety of physical training are required in volleyball, according to the characteristics of the game running at a fast tempo.…”
Section: Introductionmentioning
confidence: 99%